(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
This study was aimed at analysing factors influencing acceptance and adoption of farmer education and irrigation technology for sustainable food production as a means of ensuring food security in rural settlement of Katsina State – Nigeria. It provided insight on the underlying socio-economic factors influencing farmer’s decision to adopt education and irrigation technologies in the study area. A structured questionnaire was administered for selected farmers. Results obtained revealed that 94% of farmers were small holders with low level of education indicating that farming in the study area is highly dominated by traditional farming system that results in lower yields. It also indicates 87% of farmers were within the economic active age of 20 – 50 years. Farming experience, fragmented land holdings and poor extension services were directly related to the acceptance farmer education and adoption of irrigation technologies. The study concluded that training and educating small-scale small scale farmers that form the bulk of farming community in Nigeria are viable solutions to securing household food security, diversification of source of income and reducing rural poverty